МОДЕЛЮВАННЯ НЕЛІНІЙНОГО ПОВЕРХНЕВОГО ЕФЕКТУ МЕТОДОМ ГАРМОНІЧНОГО БАЛАНСУ СУМІСНО З МЕТОДОМ СКІНЧЕНИХ ЕЛЕМЕНТІВ ЗА УМОВ ЖИВЛЕННЯ СИНУСОЇДАЛЬНОЮ НАПРУГОЮ ТА ВИКОРИСТАННЯМ ЕФЕКТИВНИХ МАГНІТНИХ ХАРАКТЕРИСТИК - Петухов, І.С. (Інститут електродинаміки НАН України, Київ, 2018)
The nonlinear model of the time-periodic magnetic field in a conducting ferromagnetic medium is presented. The model is based on the combined use of the harmonic balance method and the finite element method. The case of magnetic field excitation by alternating sinusoidal voltage is considered. The values of eddy current losses are compared. They are determined using the method as well as monoharmonic approach with normal magnetization curve and the effective magnetic curves. It is determined that monoharmonic approach with normal magnetization curve gives the eddy current losses greater by about 9% than the losses obtained by harmonic balance method. The monoharmonic approach using effective magnetization curves gives much smaller specific eddy current losses. References 6, figures 3.